VIRULOTYPING OF LISTERIA MONOCYTOGENES ISOLATED FROM HUMAN AND FOOD PRODUCTS SAMPLES USING MULTIPLEX PCR IN DUHOK PROVINCE, IRAQ - Al-Brefkani, Azad M.; Rasheed, Narin A.; Hussein, Nawfal R. (Science Journal of University of Zakho, 2023)
Listeria monocytogenes is a facultative intracellular, food-borne zoonotic-bacterium causing life-threatening infections worldwide with a significant mortality rate in both humans and animals. The aim of the study was to examine the existence of five crucial virulence-associated genes (inIA, inIB, inIC, inIJ and prfA) in 48 L. monocytogenes isolates that were obtained from human and different food products using multiplex Polymerase Chain Reaction (PCR). The most frequent genes among isolates were inIC (93.8%), inIB (91.7%) and inIJ (83.3) followed by prfA (81.2%) and inIA (79.2%). Regardless of the source of bacteria, all tested isolates showed the prevalence of multiple virulence-associated genes. The presence of three virulence genes was detected in 20.8%, four of five virulence genes were found in 33.3% of isolates, and 45.8% of isolates carried all five virulence genes. In conclusion, the presence of potential virulence genes increases the pathogenicity of L. monocyogenes. Furthermore, the occurrence of multiple virulence related genes in a single isolate may imply the presence of highly virulent isolates. To investigate the connection between those genes and clinical outcomes, more research is needed.